Avoiding Complications in Abdominal Wall Surgery: A Mathematical Model to Predict the Course of the Motor Innervation of the Rectus Abdominis. Issue 2 (February 2016) - Tessone, Ariel; Nava, Maurizio; Blondeel, Phillip; Spano, Andrea
Abstract : Abstract: Ever since its introduction, the transverse rectus abdominis myocutaneous flap has become the mainstay of autologous breast reconstruction. However, concerns regarding donor site morbidity due to the breach of abdominal wall musculature integrity soon followed. Muscle-sparing techniques, eventually eliminating the muscle from the flap all-together with the deep inferior epigastric artery perforator flap, did not eliminate the problem of abdominal wall weakness. This led to the conclusion that motor innervation might be at fault. Studies have shown that even in the presence of an intact rectus abdominis muscle, and an intact anterior rectus sheath, denervation of the rectus abdominis muscle results in significant abdominal wall weakness leading to superior and inferior abdominal bulges, and abdominal herniation. Our aim was to establish a mathematical model to predict the location of the motor innervation to the rectus abdominis muscle, and thus provide surgeons with a tool that will allow them to reduce abdominal morbidity during deep inferior epigastric artery perforator and free muscle-sparing transverse rectus abdominis myocutaneous surgery. We dissected 42 cadaveric hemiabdomens and mapped the course of the thoracolumbar nerves. We then standardized and analyzed our findings and presented them as a relative map which can be adjusted to body type and dimensions. Our dissections show that the motor innervation is closely related to the lateral vascular supply. Thus, when possible, we support the preferred utilization of the medial vascular supply, and the preservation of the lateral supply and motor innervation.